Multimodal information architecture and artificial intelligence : applicability and architectural models - Kuroki Júnior, George Hideyuki (2023)
Tese (doutorado) — Universidade de Brasília, Faculdade de Ciência da Informação, Programa de Pós-Graduação em Ciência da Informação, 2023.